Rectus Sheath Hematoma: A Rare Surgical Emergency - Drinnon, Kyle (Cureus, 2020)
A rectus sheath hematoma (RSH) is a rare medical condition that consists of blood accumulating in the rectus abdominis muscle sheath. RSH is most frequently due to a hemorrhage from the superior or inferior epigastric artery. RSH has many specific risk factors, such as anticoagulant use. As the use of anticoagulants increases, the incidence of RSH has also increased. This condition can present with the infrequent complication of abdominal compartment syndrome (ACS), which can require surgical decompression of the abdomen to avoid high morbidity and mortality. We present the case of a 79-year-old male who, after receiving anticoagulants, developed a right-sided RSH which progressed to ACS. The patient was transferred to our care for community-acquired pneumonia, pneumothorax, and increasing respiratory support. He was admitted to the medical intensive care unit (MICU), was placed on a nasal cannula, and given vancomycin and Zosyn for pneumonia. After two days, the patient was switched to enoxaparin for anticoagulation. After three days, the patient's pneumothorax had resolved. At this time, the patient reported swelling in his right lower quadrant (RLQ) with mild pain, nausea, vomiting, and difficulty voiding completely. The physical examination confirmed RLQ swelling, and a kidney, ureter, and bladder (KUB) x-ray and ultrasound were ordered. A CT with and without contrast was also obtained which showed a large right rectus sheath hematoma extension into preperitoneal space and a small amount of intraperitoneal fluid along the right paracolic gutter. Soon after, the patient became lightheaded and fell after using the restroom. Vitals at the time were a blood pressure of 79/56, heart rate (HR) of 127, and oxygen saturation of 88% with his hemoglobin dropping from 11.4 g/dL earlier that morning to 8.4 g/dL. The patient's care was transferred to our surgical team in the surgical intensive care unit (SICU). He received an arterial line, two doses of protamine, 1-liter of crystalloids, and two units of packed red blood cells (PRBC). The patient’s vitals normalized. Interventional radiology (IR) was consulted but they requested the coagulopathy be corrected before any intervention. Reversal of his Lovenox® was thromboelastographic (TEG)-guided and included platelets, cryoprecipitate, and prothrombin complex concentrate/fresh frozen plasma (PCC/FFP), in addition to more PRBCs. During these interventions, the patient acutely decompensated with hypotension, difficulty breathing, and expansion of his hematoma. A bladder pressure in the 30s was obtained, causing him to be sent to the operating room (OR) for decompression, extraperitoneal packing, and the wound was temporarily closed. The patient returned and IR was able to embolize the right inferior epigastric artery. The patient was taken to the OR again for exploration, removal of packing, and closure. RSH is a rare complication that can occur due to trauma, coagulopathy, obesity, and muscle strains during a pregnancy. Larger hematomas tend to occur below the arcuate line because there is an absence of the posterior rectus sheath which enables the hematomas to spread. An RSH can be treated with conservative measures, but for patients who continue to bleed, more aggressive measures should be taken to avoid life-threatening complications, such as ACS.